WHISTLEBLOWING DAN FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT MELAKSANAKANNYA OLEH APARATUR SIPIL NEGARA - Lestari, Rohmaida; Yaya, Rizal (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This research aims at examining determinants of whistleblowing intentions by civil servants. The subject of this research is civil servants who work at the Ministry of Finance in Yogyakarta Regional Office whom 79 were selected based on convenience sampling method. Data were collected through questionnaire survey during October-November 2016. Based on multiple regression analysis, the result shows that personal cost and fraud seriousness are significant in influencing whistleblowing intentions by the civil servants. On the other hand ethical climate-egoism, ethical climate-benevolence, ethical climate-principle, internal locus of control and organizational commitment are not significant.